2018
DOI: 10.2147/copd.s149835
|View full text |Cite
|
Sign up to set email alerts
|

Risk of empyema in patients with COPD

Abstract: ObjectivePneumonia is one of the most common infectious diseases in patients with COPD. The risk of empyema in COPD is controversial, and its incidence has not been reported. The aim of our study was to determine the risk of empyema in COPD patients and to assess its risk factors.Patients and methodsWe used the National Health Insurance Research Database in Taiwan to conduct an observational cohort study. This study analyzed patients who were diagnosed with COPD between January 1, 2003 and December 31, 2009. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 29 publications
(27 reference statements)
0
6
0
2
Order By: Relevance
“…Diabetes mellitus has become one of the leading chronic disease burden worldwide and the overall morbidity was estimated to be 11.6% in the China [19]. Patients with diabetes mellitus were proven to have increased respiratory infectious risk due to inadequate clearance or the disturbance of normal pulmonary immune function [20]. It has been reported that diabetic patients conferred a 1.71-fold increased risk of empyema thoracis without any comorbidity [21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Diabetes mellitus has become one of the leading chronic disease burden worldwide and the overall morbidity was estimated to be 11.6% in the China [19]. Patients with diabetes mellitus were proven to have increased respiratory infectious risk due to inadequate clearance or the disturbance of normal pulmonary immune function [20]. It has been reported that diabetic patients conferred a 1.71-fold increased risk of empyema thoracis without any comorbidity [21].…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that diabetic patients conferred a 1.71-fold increased risk of empyema thoracis without any comorbidity [21]. A series of retrospective studies showed that the hazard of developing empyema was higher for patient with diabetes mellitus than those with chronic obstructive lung disease or chronic liver disease and cirrhosis [20,22]. Gosiewski T et al found the quantity of candida in the feces of patients with diabetes was signi cantly higher compared to non-diabetic controls [23].…”
Section: Discussionmentioning
confidence: 99%
“…Parasitic causes of empyema include amoebic liver abscess ruptured through the diaphragm to the pleural cavity [15]. Risk factors for developing empyema include alcohol abuse, diabetes mellitus, neoplasm, poor dentition, cerebrovascular accident, swallowing dysfunction with aspiration, underlying pulmonary disease such bronchiectasis, chronic obstructive pulmonary disease, post-obstructive pneumonia from underlying endobronchial lesion such as malignancy versus foreign body aspiration and male gender [16][17][18]. Poor host immunity or a delay in diagnosis and treatment of pneumonia might be other reasons for developing empyema.…”
Section: Discussionmentioning
confidence: 99%
“…Lu ve arkadaşları yaptıkları çalışmada PA için kronik obstrüktif akciğer hastalığı, diabetes mellitus, hipertansiyon, kronik karaciğer ve böbrek hastalıkları, inme ve kanser varlığını risk faktörü olarak bildirmişlerdir [16] . Eren ve arkadaşları ise travmanın PA için risk faktörü olduğunu bildirmişlerdir [17] .…”
Section: Bulgularunclassified
“…Etkili plevral drenaj, uygun antibiyoterapi, gereğinde cilt/cilt altı dokulara yönelik debridman/drenaj ve hastanın genel durumunun desteklenmesi tedavinin temelleridir. Tuzaklanmış akciğerin serbestlenmesi ve ekspansasyon sağlanması, medikal tedavinin etkisiz kaldığı loküle plevral odakların ortadan kaldırılması majör cerrahi için endikasyonlardır [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] . Serimizde AN hastaları genel ampiyem popülasyonuna göre daha geç opere edilmişti.…”
Section: Bulgularunclassified